2014
DOI: 10.1073/pnas.1412569111
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of gene expression as a cause of Cockayne syndrome neurological disease

Abstract: Significance Cockayne syndrome (CS) is an autosomal-recessive, multisystem disorder characterized by neurological disease, growth failure, developmental abnormalities, photosensitivity, and degeneration of organ systems such as the ear and eye, including cataracts. Most patients with CS carry mutations in Cockayne syndrome group B (CSB), best known for its role in transcription-coupled repair. Indeed, because various repair pathways are compromised in patient cells, CS is widely considered a genome i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
87
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(101 citation statements)
references
References 36 publications
(33 reference statements)
6
87
1
Order By: Relevance
“…8E). This observation may reflect an overall impact of CSB transient re-expression on nascent RNA synthesis and is consistent with the role of CSB as a chromatin remodeler in transcription in numerous genes (45,46). VCP/p97 inhibition increased RRS even in the absence of CSB induction (Fig.…”
Section: Volume 291 • Number 14 • April 1 2016supporting
confidence: 84%
“…8E). This observation may reflect an overall impact of CSB transient re-expression on nascent RNA synthesis and is consistent with the role of CSB as a chromatin remodeler in transcription in numerous genes (45,46). VCP/p97 inhibition increased RRS even in the absence of CSB induction (Fig.…”
Section: Volume 291 • Number 14 • April 1 2016supporting
confidence: 84%
“…These observations suggest that the CS proteins have other functions as well, and evidence has been provided for several other roles,5 25 including the repair of oxidative damage in DNA26–29 and roles in mitochondrial DNA metabolism 30–33. A recent elegant study, using both whole brains and cultured cells, identified a crucial role for the CS proteins in expression of neuronal genes and thereby in neuronal differentiation 34. Similar conclusions have been reached from a study in which induced pluripotent stem cell-derived neuronal cells from patients with CS had reduced transcription of many neural-specific genes 35.…”
Section: Introductionmentioning
confidence: 55%
“…Additionally, we treated the knockdown cells with the PARP inhibitor PJ34. To validate the results, we included gene expression array data from the cerebellum of human CS patients and their controls from a recently published study (19). Notably, hierarchical clustering showed an association between the CS patients and the transcription inhibitor treatments, despite batch and tissue differences.…”
Section: Significancementioning
confidence: 99%